Brainstem Raphe Alterations Depicted by Transcranial Sonography Do Not Result in Serotonergic Functional Impairment. Issue 4 (10th June 2013) - Krogias, Christos; Fischer, Gerrit; Meves, Saskia H.; Gold, Ralf; Juckel, Georg; Norra, Christine
ABSTRACT In transcranial sonography (TCS), hypoechogenic signal of mesencephalic raphe structures has been described as a frequent finding in unipolar depression. It remains unclear if raphe hypoechogenicity represents a correlate for an altered serotonergic system. The loudness dependence of auditory evoked potentials (LDAEP) has been proposed as an indirect indicator of central serotonergic activity. Aim of this study was to evaluate TCS and LDAEP as independent variables of the human cerebral serotonergic system. Sonographic and electrophysiological investigations as well as psychometric assessment were performed blindly in 44 healthy subjects (28.7 ± 7.0 years; 24 females). Hypoechogenic raphe was detected in 6 subjects (13.6%). Three probands (6.8%) exhibit hyperechogenicity of Substantia nigra. LDAEP values ranged between −2.80 and 8.40 mVeff/10dB (2.31 ± 2.44). No correlations between LDAEP and sonographic findings were found. There were no significant correlations with the psychometric assessments. At least in healthy subjects, our findings do not support the hypothesis that abnormal structural finding of hypoechogenic BR in TCS is accompanied by a functional impairment of serotonergic system as assessed by LDAEP. Further multimodal studies on patients with depressive disorders are needed to elucidate the impact of the hypoechogenic raphe signal in the pathophysiology of depression.